2019
DOI: 10.1051/0004-6361/201935357
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the damping of Alfvén waves along a long off-limb coronal loop, up to 1.4 R

Abstract: The Alfvén wave energy flux in the corona can be explored using the electron density and velocity amplitude of the waves. The velocity amplitude of Alfvén waves can be obtained from the non-thermal velocity of spectral line profiles. Previous calculations of the Alfvén wave energy flux with height in active regions and polar coronal holes have provided evidence for the damping of Alfvén waves with height. We present off-limb Hinode Extreme-ultraviolet Imaging Spectrometer (EIS) observations of a long coronal l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…The assumption of the isothermal equilibrium along the coronal part of the loop is, on one hand, motivated by observations (e.g. Gupta et al 2015;Mandal et al 2016b;Nisticò et al 2017;Gupta et al 2019), and, on the other hand, consistent with a common approach in theoretical modelling of coronal loop oscillations (e.g. Selwa et al 2005;Owen et al 2009;Mandal et al 2016a;Wang et al 2018;Wang & Ofman 2019).…”
Section: Parametermentioning
confidence: 74%
“…The assumption of the isothermal equilibrium along the coronal part of the loop is, on one hand, motivated by observations (e.g. Gupta et al 2015;Mandal et al 2016b;Nisticò et al 2017;Gupta et al 2019), and, on the other hand, consistent with a common approach in theoretical modelling of coronal loop oscillations (e.g. Selwa et al 2005;Owen et al 2009;Mandal et al 2016a;Wang et al 2018;Wang & Ofman 2019).…”
Section: Parametermentioning
confidence: 74%
“…9 in Ref. 27 and references therein for recent detections of an isothermal plasma in active regions of the solar corona. Hence, we consider an isothermal initial equilibrium, at which Q(ρ 0 , T 0 ) = 0, where the index 0 indicates the equilibrium quantities.…”
Section: Governing Equationsmentioning
confidence: 99%
“…By comparisons of the coronal Movie is available at https://www.aanda.org imaging observations in EUV or X-ray channels, together with the extrapolated field lines derived from the photospheric magnetogram, the coronal loop was found to generally follow the magnetic field line (Poletto et al 1975;Feng et al 2007). That is, a closed coronal loop usually consists of a loop apex and two footpoints that are rooted in two opposite polarities (e.g., Watko & Klimchuk 2000;Peter & Bingert 2012), while an open coronal loop connects to one apparent polarity at the solar surface and extends radially into the heliosphere magnetic field (e.g., Gupta et al 2019). Previous studies also suggested that the temperature variation along a coronal loop is highly sensitive to the heating mechanism (Priest et al 1998;Warren et al 2008).…”
Section: Introductionmentioning
confidence: 92%
“…These coronal loops often confine plasma at a temperature of mega-Kelvin, therefore they are prominently detectable in the extreme-ultraviolet (EUV) and X-ray bandpasses (Bray et al 1991;Reale 2014). Moreover, the plasmas contained in a coronal loop may be either isothermal (e.g., Del Zanna & Mason 2003;Tripathi et al 2009;Gupta et al 2019) or multithermal (e.g., Schmelz & Martens 2006;Kucera et al 2019) along the line of sight. In the corona, fully ionized plasma is frozen-in in the magnetic field line.…”
Section: Introductionmentioning
confidence: 99%